ChemInform Abstract: Selective Molecular Recognition on Calixarene‐Functionalized 3D Surfaces. Issue 50 (November 2016) - Zhang, Fan; Sun, Yue; Tian, Demei; Shin, Weon Sup; Kim, Jong Seung; Li, Haibing
Abstract: Review: 68 refs.